IMPROVING MATHEMATICS LEARNING OUTCOMES OF PYTHAGOREAN THEOREM THROUGH JIGSAW TYPE COOPERATIVE METHOD - Widana, I Wayan; Wulandari, Vidia Anting; Sudiarta, I Made (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
This research aimed to determine the extent to which the learning outcomes of class VIII G students of SMP Negeri 14 Denpasar had improved through the Jigsaw Type Cooperative learning method in learning mathematics regarding the Pythagorean Theorem. This research was classroom action research with the research subject being class VIII G of SMP Negeri 14 Denpasar Semester 1 in the academic year 2023/2024. Data on student learning outcomes was collected using written tests in the form of multiple choices. The result of this research showed that the first increase occurred in cycle I, 22 of the 42 students who took the test completed the test with a percentage of 52.4%. In cycle II, there was an increase in students who completed the test by 34 students out of 42 students who took the test with a percentage of 81%. It could be concluded that there was an increase in student learning outcomes in learning mathematics regarding the Pythagorean Theorem by applying the Jigsaw Type Cooperative learning method.